RARE-41. SECOND MALIGNANCIES FOLLOWING TREATMENT FOR PRIMARY CENTRAL NERVOUS SYSTEM TUMORS IN PEDIATRIC PATIENTS: A SINGLE-INSTITUTIONAL RETROSPECTIVE REVIEW. (4th December 2020) - Pytel, Nicholas; Dedekam, Erik; Salamat, M Shahriar; Puccetti, Diane
Abstract: Second malignant neoplasms following treatment for primary central nervous system (CNS) tumors in children are rare occurrences but may often have dire consequences, particularly, if thought to be induced by prior therapies. The authors retrospectively reviewed pediatric patients with primary CNS malignancies from the University of Wisconsin over the last 25 years (1994 – 2019) with any secondary malignant neoplasm and determined seven patients met criteria. Treatment modalities were reviewed with all patients receiving surgery, chemotherapy, and radiotherapy for treatment of their first malignancy. The second neoplasms found included 4 high-grade gliomas, 1 meningioma, 1 thyroid carcinoma, and 1 myelodysplastic syndrome. The median latency time between diagnoses was 9 years (range 4 -17 years). The outcomes varied according to histopathology of the second neoplasm with the high-grade glioma patients all deceased from progressive disease. The high-grade gliomas were thought to have been induced by prior radiation in most cases. The remaining patients are still alive, at the time of this writing, and in follow up after treatment for their second neoplasm. Thus, long-term follow up is essential for children treated for a primary CNS tumor given the variety of second neoplasms that could arise with differential consequences. In addition to our single institutional outcomes, we will also present an updated review of the literature of pediatric patients with primary CNS tumors and second malignancies.